2010
DOI: 10.1111/j.1553-2712.2010.00869.x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Posterior Vessel Wall Puncture During Ultrasound‐guided Vessel Cannulation in a Simulated Model

Abstract: Objectives: The incidence of posterior vessel wall puncture (PVWP) during central line placement with possible subsequent injury to structures lying behind the vein is unknown. At times the internal jugular vein lies immediately anterior to the carotid artery rather than lateral to it, leading to potential arterial puncture should the needle pass through the vein completely. The objective of this study is to evaluate the incidence of PVWP during simulated ultrasound (US)-guided vessel cannulation.Methods: Enro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
2
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 13 publications
0
37
2
1
Order By: Relevance
“…4 5 12 13 18 This can be explained by the fact that PVWP was considered as a complication, because under certain circumstances it can expose patients to an increased risk of developing mechanical complications. Previous clinical studies have not attempted to estimate the incidence of PVWP, although an experimental study using ultrasound phantoms suggested that it can be as high as 31% with SAX and 37% with LAX, and is not related to operator 19 The incidence of PVWP in our study was lower [eight patients (11%) with SAX and one patient (1.4%) with OAX] and not operator-related. All PVWP patients were detected after finding resistance to guidewire advance, even though the operator had initially identified the needle tip in the internal jugular lumen.…”
Section: Discussioncontrasting
confidence: 42%
“…4 5 12 13 18 This can be explained by the fact that PVWP was considered as a complication, because under certain circumstances it can expose patients to an increased risk of developing mechanical complications. Previous clinical studies have not attempted to estimate the incidence of PVWP, although an experimental study using ultrasound phantoms suggested that it can be as high as 31% with SAX and 37% with LAX, and is not related to operator 19 The incidence of PVWP in our study was lower [eight patients (11%) with SAX and one patient (1.4%) with OAX] and not operator-related. All PVWP patients were detected after finding resistance to guidewire advance, even though the operator had initially identified the needle tip in the internal jugular lumen.…”
Section: Discussioncontrasting
confidence: 42%
“…[16] IJV cannulation by emergency physicians in a simulated model (by evaluating the path of needles that had been previously placed into vascular access tissue phantoms), the incidence of posterior vein wall penetration was found to be 34%. [17] Present study was performed on humans (previous published studies have been only on mannequins or vascular tissue phantoms).…”
Section: Discussionmentioning
confidence: 99%
“…One of the key update in the standards released by the Accredential Council for Graduate Medical Education is "strategic napping" (5). The applicability of this strategic napping seems less likely for intensive care unit residents than those in other fields.…”
Section: Restricting Resident Work Hoursmentioning
confidence: 99%
“…Napping either before or during workshifts will improve performance and reduce fatigue, and has been studied in nonhealthcare and healthcare settings (though in non-ICU settings) (4,5). For example, napping was proposed as a potential solution by Drs.…”
Section: Restricting Resident Work Hoursmentioning
confidence: 99%